Nominal Wage Stickiness and the Natural Rate Hypothesis: An Empirical Analysis - Kim, Kunhong (School of Management Working Papers, 1990)
Nominal Wage Stickiness and the Natural Rate Hypothesis An Empirical Analysis Abstract This paper studies a model in which nominal wages are predetermined at the expected market clearing level, firms bear costs of adjusting labor, and households have non-time-separable utility functions. It is shown that even if nominal wages are determined one period earlier and fixed only over a period, serially uncorrelated innovations in the price level affect aggregate employment arbitrarily far into the future, Nevertheless, the model satisfies the natural rate hypothesis. The empirical result shows that the slope of the statistical Phillips curve implied by the estimates of parameters is big. The result also shows enough serial persistence in employment.